(untitled) (World Economics and Finance Bulletin, 2023)
The research aims to clarify how to apply the value engineering program, which leads to quality planning and improve product performance while reducing its cost, in addition to clarifying the importance of identifying the dimensions of product quality that the customer prefers and adding them to the priorities of the economic unit to improve the quality of service because it facilitates the process of applying engineering technology. the value . The research community is represented by the Iraqi industrial companies, while the research sample is represented by the Baghdad Company for the manufacture of packaging materials for the data of the year 2021. The research reached a set of conclusions, the most important of which was that the use of value engineering technology can help in quality planning and improve product performance by training workers in order to be able to achieve sympathy with customers in order to determine what the customer desires and needs in terms of products to work on satisfying them. Value engineering technology works to improve efficiency and search for the best balance between cost, functionality, quality, reliability and performance of the product, as well as completing operations as quickly as possible at the lowest cost and highest quality.